They both die at the end ebook - Silvera, Adam (They Both Die at the End, 2017)
Adam Silvera reminds us that there's no life without death and no love without loss in this devastating yet uplifting story about two people whose lives change over the course of one unforgettable day. #1 New York Times bestseller * four starred reviews * A School Library Journal Best Book of the Year * A Kirkus Best Book of the Year * A Booklist Editors' Choice * A Bustle Best YA Novel * A Paste Magazine Best YA Book * A Book Riot Best Queer Book * A BuzzFeed Best YA Book of the Year * A BookPage Best YA Book of the Year On September 5, a little after midnight, Death-Cast calls Mateo Torrez and Rufus Emeterio to give them some bad news: They're going to die today. Mateo and Rufus are total strangers, but, for different reasons, they're both looking to make a new friend on their End Day. The good news: There's an app for that. It's called the Last Friend, and through it, Rufus and Mateo are about to meet up for one last great adventure—to live a lifetime in a single day. In the tradition of Before I Fall and If I Stay, They Both Die at the End is a tour de force from acclaimed author Adam Silvera, whose debut, More Happy Than Not, the New York Times called "profound." Plus don't miss The First to Die at the End: #1 New York Times bestselling author Adam Silvera returns to the universe of international phenomenon They Both Die at the End in this prequel. New star-crossed lovers are put to the test on the first day of Death-Cast's fateful calls.